2015
DOI: 10.1007/s00253-014-6358-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect and behaviour of different substrates in relation to the formation of aerobic granular sludge

Abstract: When aerobic granular sludge is applied for industrial wastewater treatment, different soluble substrates can be present. For stable granular sludge formation on volatile fatty acids (e.g. acetate), production of storage polymers under anaerobic feeding conditions has been shown to be important. This prevents direct aerobic growth on readily available chemical oxygen demand (COD), which is thought to result in unstable granule formation. Here, we investigate the impact of acetate, methanol, butanol, propanol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(93 citation statements)
references
References 60 publications
3
74
1
15
Order By: Relevance
“…Aerobic granules are also characterised by their layered structure. The 49 presence of an aerobic outer layer and an anaerobic or anoxic core, facilitates co-existence of 50 nitrifying organisms in the outer layers of the granules and denitrifying phosphate 51 accumulating organisms (dPAO), as well as (facultative) anaerobic organisms towards the 52 centre of the granules (Gieseke et al 2001, Winkler et al 2012, Pronk et al 2015. Due to 53 this structure, aerobic granular sludge can simultaneously remove phosphorus, nitrogen and 54 COD (chemical oxygen demand) from the liquid (de Kreuk et al 2005, Gonzalez-Gil and 55 Holliger 2011).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Aerobic granules are also characterised by their layered structure. The 49 presence of an aerobic outer layer and an anaerobic or anoxic core, facilitates co-existence of 50 nitrifying organisms in the outer layers of the granules and denitrifying phosphate 51 accumulating organisms (dPAO), as well as (facultative) anaerobic organisms towards the 52 centre of the granules (Gieseke et al 2001, Winkler et al 2012, Pronk et al 2015. Due to 53 this structure, aerobic granular sludge can simultaneously remove phosphorus, nitrogen and 54 COD (chemical oxygen demand) from the liquid (de Kreuk et al 2005, Gonzalez-Gil and 55 Holliger 2011).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…AGS have been successfully implemented for the treatment of both municipal and industrial wastewater. The literature studies demonstrated that aerobic granules feature a compact and thick structure, thus ensuring a great ability to withstand adverse environmental conditions, such as loading variation, obtaining very high effluent quality at the same time [17][18][19][20]. Indeed, the granular sludge features very high settling ability and allows to maintain higher biomass concentrations, thus reducing the plant footprint [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among those, the impacts of the VFA composition on PAO and GAO metabolisms and selection (Gonzalez-Gil and Holliger, 2011;Lopez-Vazquez et al, 2009;Weissbrodt et al, 2013b), and of different ranges of substrates and salinities on additional microbial processes can be studied (Pronk et al, 2014(Pronk et al, , 2015aWelles et al, 2014). Among those, the impacts of the VFA composition on PAO and GAO metabolisms and selection (Gonzalez-Gil and Holliger, 2011;Lopez-Vazquez et al, 2009;Weissbrodt et al, 2013b), and of different ranges of substrates and salinities on additional microbial processes can be studied (Pronk et al, 2014(Pronk et al, , 2015aWelles et al, 2014).…”
Section: Model Integration In Ebpr Granular Sludge Research and Practicementioning
confidence: 99%
“…Model extensions can provide opportunities for solving multiple research questions. Among those, the impacts of the VFA composition on PAO and GAO metabolisms and selection (Gonzalez-Gil and Holliger, 2011;Lopez-Vazquez et al, 2009;Weissbrodt et al, 2013b), and of different ranges of substrates and salinities on additional microbial processes can be studied (Pronk et al, 2014(Pronk et al, , 2015aWelles et al, 2014). Latest molecular and ecophysiology investigations further highlighted that engineered EBPR microbial ecosystems consist of a diversity of populations within the PAO and GAO guilds, which could be considered in model extensions as well (Albertsen et al, 2016;Forbes et al, 2009;Lanham et al, 2013;Nielsen et al, 2012;Weissbrodt et al, 2014c;Welles et al, 2015).…”
Section: Model Integration In Ebpr Granular Sludge Research and Practicementioning
confidence: 99%